PENGEMBANAN FLIP BOOK IPAS HARMONI KEHIDUPAN: KEBUTUHAN MANUSIA DAN PERAN TUMBUHAN UNTUK KELAS IV SD - Pawartani, Transita; Suciptaningsih, Oktaviani (Study program PGSD FKIP Universitas Bung Hatta, 2024)
The merging of natural science and social science is directed to help students understand the complexity of the relationship between natural elements and social factors in an integrated context, thus assisting in building a deeper understanding of the world around them. The purpose of this study was to develop an interactive flip book that can understand social knowledge and natural knowledge in an integrated manner for grade IV students. The research method uses the Richey and Klein model, namely Research, Design, Production and Evaluation. The data analysis technique uses quantitative descriptive analysis techniques. The results showed that based on the results of media validators and material validators flip book is valid for use as learning media. Based on the results of the IPAS Flip Book trial, it has a positive effect on student learning achievement results.